Kerala's progress towards universal health coverage: the road travelled and beyond - G.S. Adithyan; Alok Ranjan; V. R. Muraleedharan; T. Sundararaman (BMC, 2024)
Abstract Background Kerala has initiated many Universal Health Coverage (UHC) reforms in the last decade. The Aardram Mission launched in 2017 stands out owing to its scope, objectives, and commitments for strengthening Primary Health Care (PHC) in the State. The current study proposes to explore access and financial protection through the lens of equity in Kerala especially in the context of major UHC reforms carried out during the last decade. This paper will also highlight the key lessons from Kerala's approach towards UHC and health systems strengthening through a political economy approach. Methods Data from the Kerala state sample of 75th Round (2017-18) National Sample Survey is used for this study. Comparison is also drawn from the 71st Round Sample Survey, 2014, to measure the state's progress in terms of access and financial protection. Logistic regression was used for the calculation. The findings were further explored through a political economy approach. Results The share of public facilities for outpatient care is 47.5%, which is a significant increase from 34.0% (in 2014) in the state. The share of public sector for out-patient care has increased for the lower socio-economic population in the state. The share of public sector for in-patient care has also increased to 37.3% in 2017-18 from 33.9% in 2014, but not to the extent as the increase shown in outpatient care. The average out-of-pocket-expenditure during hospitalization has increased more in private facilities as compared to public for both outpatient care and hospitalization. Conclusions Overall increase in the share of public facilities for both outpatient care and hospitalization is indicative of the enhanced trust among the people at large of the public healthcare delivery system in Kerala, post the launch of UHC reforms in the State. The insurance linked UHC reforms would be insufficient for the State to progress further towards UHC. Kerala with a long and successful history in 'public provisioning' should focus more on strengthening PHC through Aardram Mission in its journey towards pursuit of UHC.